LIQUID-LIQUID EXTRACTION AND SPECTROPHOTOMETRIC CHARACTERIZATION OF SOME NEW TERNARY IONASSOCIATION COMPLEXES OF COBALT (II) AND NICKEL (II) - Zalov, Ali Z.; Gasimova, Yavar C.; Ibrahimova, Shala A. (IJRDO-Journal of Applied Science, 2016)
Complex formation and liquid-liquid extraction were studied in systems containing M(II) (M= cobalt or nickel), 2-hydroxy-5-iodothiophenol (HITP), hydrophobic amines (Am), waterand chloroform. Two different Am were used: diphenylguanidine (DPG) andtriphenylguanidine (TPG).The optimum conditions for extraction of Co(II) and Ni(II) asternary complexes with the general formula [M(HITP)2](AmH+)2 were found: pH, shakingtime, concentration of HITP and concentration of Am. Some key constants (constants ofextraction – Kex, constants of association – β, constants of distribution – KD) and analyticalcharacteristics (molar absorptivities – εmax, Sandell’s sensitivities – SS, limits of detection –LOD, limits of quantification – LOQ, etc.) were determined.